Networked Control Over Noisy Channel With Time Delays - Qing-Quan Liu; Fang Jin (Institute of Advanced Engineering and Science, 2014)
This paper investigates networked control problems for linear control systems, where the sensors and the controller are connected by a bandwidth-limited, noisy digital communication channel with time delays. For this case, we examine the role communication has onquantized feedback stabilization problems, present quantization, coding, and control schemes, and derive a sufficient condition on the data rate of stabilization of the unstable plant. It is shown in our results that, communication constraints have important effectson stabilization of networked control systems. An illustrative example is given to demonstrate the effectiveness of the proposed method. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3816